Draft Genome Sequence of Pseudomonas toyotomiensis KF710, a Polychlorinated Biphenyl-Degrading Bacterium Isolated from Biphenyl-Contaminated Soil - Watanabe, Takahito (Genome Announc, 2015)
Pseudomonas toyotomiensis KF710 utilizes biphenyl and degrades polychlorinated biphenyls (PCBs). Here, we report the genome sequence of the KF710 strain, consisting of 5,596,721 bp with 5,155 coding sequences. The biphenyl catabolic genes were almost identical to those of Pseudomonas pseudoalcaligenes KF707, one of the most well-characterized biphenyl-utilizing strains.